The EU – Ukraine Relations through the Prism of Human Rights (Economic and Political Thought, 2013)
The research: (1) embraces peculiarities of the current EU foreign policytowards Ukraine; (2) enumerates and analyzes documents, agreements andtreaties which establish the frameworks for this policy; (3) discovers theimpact of human rights issues on shaping and conducting this policy. Basedon the criminal trials against opposition leaders, the analysis is provided toestablish to what extent the human rights violation in Ukraine can worsenthe relations between Kyiv and Brussels in the current context. As a result,several key factors which can alter the EU foreign policy towards Ukraineare pointed out.